Maternal and perinatal outcome in obstetric cholestasis- a prospective observational study - Anand, Ruma S.; Khan, Naghma; Malik, Najma; Aditya, Vani; Singh, Reeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to study the maternal and perinatal outcome of pregnancy complicated by obstetric cholestasis. Methods: This prospective observational study included 80 cases, diagnosed as obstetric cholestasis on the basis of symptoms of persistent pruritus (generalized or localized), biochemical evidence of altered liver function test and excluding other liver and skin disorder. Medical treatment and active management (fetal surveillance and termination of pregnancy at 37-38 weeks) were offered to all. Maternal and perinatal outcome were studied. Results: Incidence of obstetric cholestasis was 1.9%. Majority of women (55%) were primigravida and recurrence rate was 61.1% among multiparous women. Pruritus (generalized) was the cardinal symptoms in 90% patients and mostly (88.7%) presented and diagnosed after 28 weeks i.e. in third trimester. A total of 43.7%women had caesarean section (CS) which was quite high incidence. Most common pregnancy complications included preterm labor (25%), post-partum haemorrhage (13.75%) and preterm premature rupture of membrane (11.25%). Perinatal outcome revealed meconium aspiration (20%), preterm birth (30%), low birth weight (35%), fetal distress (18.75%) and intrauterine fetal death (2.5%). 43.75% neonates required NICU (Neonatal intensive care unit) admission. Serum transaminase levels tended to be higher in patients with poor perinatal outcome such as still birth, fetal distress and meconium stained amniotic fluid. LFT (liver function test) returned to normal in 95% of women and 100% women became symptom free after 6 weeks postpartum. Conclusions: Obstetric cholestasis has an adverse effect on the fetal outcome and hence early diagnosis with careful clinical examination and biochemical testing is essential. Serum abnormality in liver function test (transaminases) tended to be higher in women with poor perinatal outcome.